Determinants of the Green Purchase Intention in Jordan: The Moderating Effect of Environmental Concern - Al- Quran, Ali Zakariya; Alhalalmeh, Mohammad Izzat; Eldahamsheh, Mohammad Mousa; Mohammad, Anber Abraheem Shlash; Saed Hijjawi, Ghufran; Almomani, Hanan Mohammad; Al-Hawary, Sulieman Ibraheem Shelash (ExcelingTech, 2020)
Abstract The purpose of the paper is to evaluate the impact of environmental attitude, green satisfaction, green trust, and green perceived quality on Green Purchase Intention (GPI) with the moderation of Environmental Concern (EC) in the fast moving consumer goods. The FMCG industry of Jordan was targeted to collect data. The quantitative approach was adopted for collecting data with using purposive sampling. The PLS-SEM analysis was implemented using SmartPLS 3.2.8. Environmental attitude and green perceived quality have positive but statistically insignificant effect on GPI while green satisfaction and green trust have positively significant effect on GPI. Furthermore, the effect of environmental attitude, green perceived quality, green satisfaction, and green trust have been positively moderated by the EC. Establishing and pushing pro-environmental tendencies with the help of increasing environmental awareness is one of the most important factors in the developing countries also including Jordan.